Bladder Base Tenderness in the Etiology of Deep Dyspareunia. (21st September 2014) - Nourmoussavi, Melica; Bodmer‐Roy, Sonja; Mui, Justin; Mawji, Narissa; Williams, Christina; Allaire, Catherine; Yong, Paul J.
Abstract Introduction Bladder base tenderness can be present on pelvic exam in women with pelvic pain. However, its exact prevalence and clinical implications are not well understood. Aim The aim of this study was to determine whether bladder base tenderness is associated with specific symptoms or signs in women, particularly dyspareunia. Methods Retrospective review of 189 consecutive women seen by a gynecologist in 2012 at a tertiary referral center for pelvic pain was conducted. Associations were tested between bladder base tenderness and variables on history/examination using bivariate analyses and multiple logistic regression. Main Outcome Measure Deep dyspareunia and superficial dyspareunia (present/absent) were the main outcome measures. Results Bladder base tenderness was present in 34% of pelvic pain patients (65/189), which was significantly greater than the prevalence of bladder base tenderness of 3% (1/32) in a control sample of women without pelvic pain (odds ratio [OR] = 16.3, 95% confidence interval [CI] 2.17–121.7, Fisher exact test, P < 0.001). For the pelvic pain patients, on bivariate analyses, bladder base tenderness was significantly associated with deep dyspareunia (P < 0.001), superficial dyspareunia (P < 0.001), bladder symptoms (P = 0.026), abdominal wall trigger point (P < 0.001), and pelvic floor tenderness (P < 0.001). In contrast, bladder base tenderness was similarly present in women with or without endometriosis. On logistic regression, bladder base tenderness was independently associated with only deep dyspareunia (OR = 6.40, 95% CI: 1.25–32.7, P = 0.011), abdominal wall trigger point (OR = 3.44, 95% CI: 1.01–11.7, P = 0.037), and pelvic floor tenderness (OR = 8.22, 95% CI: 3.27–20.7, P < 0.001). Conclusions Bladder base tenderness is present in one‐third of women with pelvic pain, and contributes specifically to the symptom of deep dyspareunia. Bladder base tenderness was also associated with the presence of an abdominal wall trigger point and with pelvic floor tenderness, suggesting a myofascial etiology and/or nervous system sensitization. Nourmoussavi M, Bodmer‐Roy S, Mui J, Mawji N, Williams C, Allaire C, and Yong PJ. Bladder base tenderness in the etiology of deep dyspareunia. J Sex Med 2014;11:3078–3084.